Ecoterritorialismo - Magnaghi, Alberto; Marzocca, Ottavio (Territori, 2023)
Eco-territorialism is the mature definition of the long scientific research/action path that the Italian territorialist school started in the 1990s, putting the territory and its patrimonialisation at the centre of the alternatives to processes of deterritorialisation and homologising urbanisation of the planet enacted by the economic-financial globalisation. The founding in 2011 of the Territorialist Society has strengthened the multidisciplinary nature of the approach and its operational component with the 'urban bioregion' tool. The 'eco' prefix denotes the priority given to the ecological question, to the relationships between human and non-human, living and non-living, in the regeneration processes of the world's places we are trying to activate.